2012
DOI: 10.1016/j.freeradbiomed.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Systemic oxidative stress is implicated in the pathogenesis of brain edema in rats with chronic liver failure

Abstract: Chronic liver failure leads to hyperammonemia, a central component in the pathogenesis of hepatic encephalopathy (HE); however, a correlation between blood ammonia levels and HE severity remains controversial. It is believed oxidative stress plays a role in modulating the effects of hyperammonemia. This study aimed to determine the relationship between chronic hyperammonemia, oxidative stress, and brain edema (BE) in two rat models of HE: portacaval anastomosis (PCA) and bile-duct ligation (BDL). Ammonia and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 48 publications
8
94
0
Order By: Relevance
“…Wright et al, using electron microscopy, precisely demonstrated that the BBB is anatomically intact in BDL rats (Wright et al, 2007). Furthermore, in the same model, our group did not find any brain extravasation of Evans Blue or sodium fluorescein (Bosoi et al, 2012), nor any changes in the expression of the tight junction proteins (Huynh et al, 2011). In another rat model of chronic HE, induced by a portacaval anastomosis (PCA), breakdown of the BBB could also not be demonstrated (Alexander et al, 2000).…”
Section: Vasogenic Versus Cytotoxic Brain Edema In Alf and Cldsupporting
confidence: 61%
See 4 more Smart Citations
“…Wright et al, using electron microscopy, precisely demonstrated that the BBB is anatomically intact in BDL rats (Wright et al, 2007). Furthermore, in the same model, our group did not find any brain extravasation of Evans Blue or sodium fluorescein (Bosoi et al, 2012), nor any changes in the expression of the tight junction proteins (Huynh et al, 2011). In another rat model of chronic HE, induced by a portacaval anastomosis (PCA), breakdown of the BBB could also not be demonstrated (Alexander et al, 2000).…”
Section: Vasogenic Versus Cytotoxic Brain Edema In Alf and Cldsupporting
confidence: 61%
“…Our group recently demonstrated, in six-week BDL rats, that brain edema develops in the presence of systemic, and not cerebral, oxidative stress ( Bosoi et al, 2012). This systemic phenomenon was confirmed as the attenuation of systemic oxidative stress using allopurinol (xanthine oxidase inhibitor) led to a reduction in brain edema ( Bosoi et al, 2012). In the same animal model, our group demonstrated that blood ammonia and oxidative stress are independent factors, and are synergistically implicated in the development of brain edema ( Bosoi et al, 2012).…”
Section: Oxidative Stressmentioning
confidence: 61%
See 3 more Smart Citations